Lunatic carnival - Buffa, Dudley W., 1940- (Buffa, Dudley W., 1940- Joseph Antonelli novels, 2023)
A professional athlete, T.J. Allen, is charged with the murder of Matthew Stanton, the owner of the team. Antonelli agrees to take the case only after the trial court judge tells him that Allen is innocent and that "All of America contributed to the making of Matthew Stanton." The evidence is firmly stacked against Allen: he was found standing over Stanton's dead body, the murder weapon still in hand. The only way to prove Allen is innocent it is to find the real killer and their motive. Who had a reason to kill Matthew Stanton? What had he done, or what was he planning to do, that made the real killer think he had no choice? As Joseph Antonelli prepares for the most difficult case of his career, he will learn that the answer to that question will change not only the outcome of this trial, but could change the world as we know it.